Pengembangan LKPD Berbasis Kearifan Lokal Nusa Penida pada Materi Teks Negosiasi Kelas X - Made Yeni Kusumayanthi; I Wayan Rasna; I Ketut Paramarta (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to decipher and explain the characteristics, validity, practicality, and effectiveness of LKPD based on Nusa Penida local wisdom in class X negotiation text. The development model used is a 4-D model but only includes the stages of define, design, and develop. Data collection was carried out using questionnaire and test techniques. The results of the validity test show that the resulting LKPD is classified as very valid in terms of content (material), graphics, and language. Based on the assessment of teachers and students, the LKPD is classified as very practical. The results of the effectiveness test show that the LKPD can improve student learning outcomes. Thus, the LKPD is based on the local wisdom of Nusa Penida on the class X negotiation text material that is valid, practical, and effective.